Diagnosis and management of gastric dysplasia - Sung, Jae Kyu (The Korean journal of internal medicine, 2016)
Gastric dysplasia is a neoplastic lesion and a precursor of gastric cancer. The Padova, Vienna, and World Health Organization classifications were developed to overcome the discrepancies between Western and Japanese pathologic diagnoses and to provide a universally accepted classification of gastric epithelial neoplasia. At present, the natural history of gastric dysplasia is unclear. Much evidence suggests that patients with high-grade dysplasia are at high risk of progression to carcinoma or synchronous carcinoma. Therefore, endoscopic resection is required. Although patients with low-grade dysplasia have been reported to be at low risk of progression to carcinoma, due to the marked histologic discrepancies between forceps biopsy and endoscopic specimens, endoscopic resection for this lesion is recommended, particularly in the presence of other risk factors (large size; depressed gross type; surface erythema, unevenness, ulcer, or erosion; and tubulovillous or villous histology). Helicobacter pylori eradication in patients with dysplasia after endoscopic resection appear to reduce the incidence of metachronous lesions.